2020
DOI: 10.1186/s40594-020-00209-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of school climate and teacher self-efficacy on job satisfaction of mostly STEM teachers: a structural multigroup invariance approach

Abstract: Background: Identification and retention of effective teachers in STEM education play cardinal roles in teacher recruitment exercises worldwide. Studies on factors that characterize effective teachers have therefore gained popularity in recent times. Teacher self-efficacy, job satisfaction and school climate are among other factors that have attracted global attention. Thus, proper understanding of the relations between these factors is equally important. The purpose of this study is to validate and cross-vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
53
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 34 publications
(55 reference statements)
14
53
1
1
Order By: Relevance
“…The result that the perception of self-efficacy has a direct and positive effect on job satisfaction, found in this research, is parallel to the results of the study conducted by Zakariya (2020). Zakariya (2020) used TALIS 2018 data of the Norwegian middle school teachers in his research and found that self-efficacy directly affects job satisfaction.…”
Section: Discussionsupporting
confidence: 84%
“…The result that the perception of self-efficacy has a direct and positive effect on job satisfaction, found in this research, is parallel to the results of the study conducted by Zakariya (2020). Zakariya (2020) used TALIS 2018 data of the Norwegian middle school teachers in his research and found that self-efficacy directly affects job satisfaction.…”
Section: Discussionsupporting
confidence: 84%
“…They should have well-prepared in integrated STEM education and other supporting to reach the requirement of integrated instruction. However, the implementation of STEM education in school need to be clearer and strengthen to the collaborative work (Bush et al, 2020;Zakariya, 2020;Permanasari et al, 2021). Teachers might want to have positive perception and attitudes toward integrated approaches especially STEM education in different learning contexts (Rose et al, 2017;Margot & Kettler, 2019;Daher & Shahbari, 2020;Kelly et al, 2020;Nguyen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the school principal's academic supervision, another thing that can affect teacher performance is the work climate at schools (Zakariya, 2020). The working climate in a school or madrasa is a situation around a school or madrasa in a calm and comfortable atmosphere and conducive to learning that can increase academic achievement (MacNeil, Prater, & Busch, 2009).…”
Section: There Is An Indirect Relationship Between School Principal Smentioning
confidence: 99%